Sneathia infections and adverse perinatal outcomes – short communication - Valentin Varlas; Vlad Dima; Roxana Georgiana Bors (Romanian Journal of Infectious Diseases, 2022)
The influence of the maternal vaginal microbiome in vaginal birth is an important factor in the pathogenesis of early-onset neonatal sepsis. The incidence of Sneathia infection is hard to assess due to the difficulty in its detection, as special culture conditions are required. The laboratory methods used in its detection are based on molecular analysis. This emergent, anaerobic agent, by ascending from the female genital tract, can colonize and infect the amniotic fluid, fetal membranes, and placenta. Chorioamnionitis, neonatal sepsis, stillbirth, spontaneous premature labor, and preterm prelabour rupture of the membrane are some of the adverse reactions that can be associated with the presence of Sneathia. In conclusion, Sneathia infection, although underestimated due to its virulence, represents an increased risk of maternal-fetal infections, with the risk of developing a series of neonatal complications. The detection and treatment of this infection will contribute to a decrease in neonatal morbidity and mortality.